Nepal’s Water Resource Development Challenges - Bhusal, Jagat K. (State, Society and Development: PMPD Perspectives, 2024)
Water resources of Nepal represent one of its most valuable renewable natural assets. This paper examines the challenges and opportunities inherent in the development of Nepal’s water resources, with a specific focus on the cooperation between Nepal and India. Additionally, it delves into the water resource development policy from the perspective of People’s Multiparty Democracy (PMPD). Harnessing Nepal’s water resources optimally, particularly through hydroelectricity, irrigation, and floodwater storage, holds immense potential for bolstering the country’s economic growth and fostering socio-economic advancement in the broader South Asian region. However, issues surrounding water resources have emerged as a significant point of contention between Nepal and India. This paper critically evaluates Nepal’s bilateral agreements on water resources, particularly those with India, and explores comparative practices within similar geographic contexts. It identifies parallels between the global understanding of integrated water resources management policy and the principles outlined in PMPD policy.